MODEL PEMBELAJARAN TERHADAP MINAT DAN HASIL BELAJAR ILMU PENGETAHAUAN SOSIAL - Desye Trimasyusiati (Herodotus: Jurnal Pendidikan IPS, 2019)
The purpose of this study was to determine the extent of the influence of the use of learning models and interest in learning on social studies learning outcomes, especially in social studies for MTs students. If indeed there is a positive and significant influence, how strong is the influence of using learning models and interest in learning on learning outcomes in social studies subjects. The research model used is experimental and the analysis model is treatment by level. The type of test used is Manova. Experiments were carried out in two groups / samples where each group was given a different treatment. The first group was taught using the Jigsaw model, while the second group was taught using conventional learning models. Each group is further divided into two categories according to the type of interest in learning, namely groups that have high and low learning interest. Data about interest in learning and student learning outcomes through tests on respondents. The test is carried out directly by the researcher, for the interest in learning test is carried out before the learning process, while the learning outcome test is carried out after the learning process is complete. The results of the study: 1) There is a significant effect of the multivariate learning model on the interest and social science learning outcomes of MTs Negeri students in the city of Jakarta. This is evidenced by the acquisition of sig = 0.000 <0.05 and Fcount = 15.1510. 2) There is a significant effect of the learning model on the learning interest of State MTs students in the city of Jakarta. This is evidenced by the acquisition of sig = 0.000 <0.05 and Fcount = 22.905. 3) There is a significant influence of the learning model on social studies learning outcomes of State MTs students in the city of Jakarta. This is evidenced by the value of sig = 0.000 <0.05 and Fcount = 16.555.